2022
DOI: 10.3390/socsci11100487
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Teachers’ Expectations of School Social Workers

Abstract: In parallel with research focusing on the effectiveness of students and teachers, the content and impact of school social work have come to the forefront of international research discourses. In the Hungarian public education system, teachers had previously carried out social assistance tasks, but in September 2018, an external model of kindergarten and school social assistance activities was introduced, giving structure to the already existing work. No empirical studies have been performed on the results of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Special education teachers have a key role in parent-school relationships, as best illustrated by Bronfenbrenner's ecological model, as they are responsible for the design and implementation of educational, health, and developmental programs at the micro level but also play an important role in the day-to-day interactions between families and children. The latter can be facilitated by other helping professionals working in and out of school [64]. At the micro level, they are also responsible for implementing education policy plans.…”
Section: Discussionmentioning
confidence: 99%
“…Special education teachers have a key role in parent-school relationships, as best illustrated by Bronfenbrenner's ecological model, as they are responsible for the design and implementation of educational, health, and developmental programs at the micro level but also play an important role in the day-to-day interactions between families and children. The latter can be facilitated by other helping professionals working in and out of school [64]. At the micro level, they are also responsible for implementing education policy plans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Asian parents appear to be the less or the least involved parents compared to other ethnic groups or to the majority, especially when it comes to the frequency of attending school-based activities, while the same group is more active compared to other groups when it comes to home-based functions (Kim et al 2018). Also, the language barrier is another hindering factor which further disempowers minoritized groups, something apparent in empirical research (Gkaintartzi et al, 2020;Androulakis et al, 2018;Bloch & Hirsch, 2017), especially when there are no provisions of professional interpreters in schools or a shared language (Cline et al, 2014) or of social workers (Csók & Pusztai, 2022). In this context, children assume this role and become interpreters for their parents, which disrupts traditional perceptions of agency, power and control shared among parents and children (McWayne, 2019;Bloch & Hirsch, 2017).…”
Section: Home-school Communicationmentioning
confidence: 99%
“…Ozmen and his colleagues (2016), in their examination of the factors hindering the effectiveness of communication between teachers and parents, concluded that a fundamental prerequisite for effective and successful education is the seamless communication among teachers, between teachers and the institution's leadership, with students, and between parents and teachers. During their qualitative investigation, Csók and Pusztai (2022) also observed communication challenges between teachers and parents. They believe that social work professionals can contribute to positive changes in communication.…”
Section: Problems Occurring In Communicationmentioning
confidence: 99%